Calciphylaxis: Successful Management of a Rare Complication of Chronic Kidney Disease in Two Patients. (17th June 2019) - Fares, Ibtissam; Bouattar, Tarik; Kone, Hadja Moussokoro; Benzouina, Hajar; Benbella, Meryem; Ouzeddoun, Naima; Bayahia, Rabia; Benamar, Loubna
Abstract : Calciphylaxis, or calcification uremic arteriolopathy, is a rare disease thought to occur due to arteriolar calcifications of the dermis and is responsible for ischemia with cutaneous necrosis and painful panniculitis. Its mechanism remains poorly understood which makes its management challenging and difficult to standardize. We report our management of two patients diagnosed with calciphylaxis. In one patient, calciphylaxis was mentioned upon admission given the context of preexisting secondary hyperparathyroidism and the existence of multiple risk factors. In both patients, the diagnosis was confirmed histologically. Our two observations highlight the difficulty of the diagnosis and the complexity of the therapeutic management that has been personalized according to patient characteristics and clinical evolution. Several therapeutic means can be implemented once the diagnosis is made; nevertheless, its prognosis remains pejorative despite the therapeutic advances. Broad debridement, good phosphocalcic balance control, and the correction of the risk factors top the list of any therapeutic strategy. One of the major challenges of the therapy is normalizing the calcium-phosphate balance. Thus, Cinacalcet and sodium thiosulfate appear to be promising treatments.